Myrosinase activity in microorganisms and its possible health benefits for humans & potential antibacterial effect of marine biological waste products - Ingman, Caroline (2009)
Cancer is an illness that affects countless persons, either they themselves are afflicted or someone in their vicinity is. Research has shown that when glucosinolates – secondary metabolites in plants from the Brassicaceae family – are degraded in the stomach of animals via the enzyme (myrosinase), their metabolites can counteract the formation of tumour cells. However, the natural degradation in the stomach might not be sufficient, so it has been proposed that intake of microbes with myrosinase activity might be beneficial for the degradation of glucosinolates. This study was therefore conducted to search for microbes with myrosinase activity that might be safely digested.